THE CONCEPT OF COMMUNITY-BASED ISLAMIC EDUCATION - Wulandari Wulandari; M. Tahir; Zamroni Zamroni (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
Community-based Islamic education is an educational model that positions the community as an active participant in the learning process. This concept emphasizes that education is not solely the responsibility of the government but also a social and moral obligation of the community. This education is grounded in Islamic philosophical values, local wisdom, and national regulations such as Law Number 20 of 2003 and Government Regulation Number 55 of 2007. Sociologically, community-based education strengthens mutual cooperation and the relevance of education to social needs. Religiously, this education encourages the development of a knowledgeable and beneficial generation. Thus, community-based Islamic education plays a crucial role in strengthening Islamic identity, increasing community participation, and realizing equitable and civilized education.